AI for finance - Tsang, Edward (AI for everything, 2023)
"Finance students and practitioners may ask: Can machines learn everything? Where could AI help me? Computing students or practitioners may ask: which of my skills could contribute to finance? Where in finance should I pay attention? This book aims to answer these questions. No prior knowledge is expected in AI or finance. To finance students and practitioners, this book will explain the promise of AI and its limitations. It will cover knowledge representation, modelling, simulation and machine learning. It will explain the principle of how they work. To computing students and practitioners, this book will introduce the financial applications in which AI has made an impact. This includes algorithmic trading, forecasting, risk analysis portfolio optimization and other less well-known areas in finance. This book trades depth for readability. It aims to help readers to decide whether to invest more time into the subject. This book contains original research. For example, it explains the impact of ignoring computation in classical economics. It explains the relationship between computing and finance and points out potential misunderstandings between economists and computer scientists. It introduces Directional Change and explains how it can be used"--